Revisiting the Utility of Dilated Fundus Exams in Patients with Neovascular Age-Related Macular Degeneration Receiving Regular Intravitreal Injections - Antaki F (Dove Medical Press, 2021)
Fares Antaki,1,2 Daniel Milad,3 Ali Dirani4 1Department of Ophthalmology, Université de Montréal, Montreal, QC, Canada; 2Centre Universitaire d’Ophtalmologie (CUO), Hôpital Maisonneuve-Rosemont, CIUSSS de l’Est-De-l’île-De-Montréal, Montreal, QC, Canada; 3Faculty of Medicine, Université Laval, Quebec City, QC, Canada; 4Department of Ophthalmology, Centre Universitaire d’Ophtalmologie, Hôpital du Saint-Sacrement, CHU de Québec - Université Laval, Quebec City, QC, CanadaCorrespondence: Ali DiraniDepartment of Ophthalmology, Centre Universitaire d’Ophtalmologie, Hôpital du Saint-Sacrement, CHU de Québec - Université Laval, Quebec City, QC, CanadaEmail drdirani@gmail.comAbstract: Patients receiving regular anti-vascular endothelial growth factor (anti-VEGF) intravitreal injections for neovascular age-related macular degeneration (nAMD) routinely undergo dilated fundus examination (DFE) at each visit. In this paper, we review the current evidence on the utility of DFE in guiding treatment of established patients with nAMD and discuss novel treatment algorithms that defer DFE assessments with the advent of optical coherence tomography (OCT). We also debate on the value of DFE in the current sanitary context of COVID-19 and highlight important clinical scenarios where it must be performed.Keywords: age-related macular degeneration, dilated fundus exam, intravitreal injections, COVID-19, optical coherence tomography